Odpowiedzi

2010-03-02T17:59:44+01:00
4(y-3)-3(x+1) dla x=4,y=2
4y-12-3x-3 = 4y-3x-15
4y-3x-15 = 4*2 - 3 *4 -15 = 8-12-15 = -19

3(2b+1)-4(a-2) dla a=7,b=1
6b+3-4a+8 = 6b+11-4a
6b+11-4a = 6 * 1 +11-4*7 = 6+11-28 = -11

9(x-7y)-(5y-2x)+20y dla x=0,5, y=0,3
9x-63y-5y+2x+20y = 11x-48y
11x-48y = 11 * 0,5 - 48 * 0,3 = 5,5-14,4 = -8,9
36 4 36
  • pewi
  • Początkujący
2010-03-02T18:01:22+01:00
Wykonaj działania i oblicz wartość liczbową wyrażenia.
4(y-3)-3(x+1) dla x=4,y=2
4(2-3)-3(4+1)=4*(-1)-3*5=-4-15=-19

3(2b+1)-4(a-2) dla a=7,b=1
3(2*1+1)-4(7-2)=3*3-4*5=9-20=-11

9(x-7y)-(5y-2x)+20y dla x=0,5, y=0,3
9(0,5-7*0,3)-(5*0,3-2*0,5)+20*0,3= 9(0,5-2,1)-(1,5-1)+6= 9*(-1,6)-0,5+6= -14,4+5,5= -8,9

1 1
(5x+7y)-8(y+1)+3(x-y dla x= - 2, y= -4
(-10-28)-8(-3)+3*2= -38+32+6=0
18 4 18
2010-03-02T18:03:03+01:00
4y-3x-15=4*2-3*4-15=8-12-15=-19
6b-4a+11=6-28+11=-11
11x-48y=11*0,5-48*0,3=5,5-14,4=-8,9
10 3 10